Medicine Costs of Chronic Diseases Outpatient in an Indonesian Hospital Under National Health Insurance - Rambe, Rima; Intan Farah Diba Angela; Khairunnisa, Khairunnisa; Simangunsong, Angelia Debora Moria (Public Health of Indonesia, 2025)
Background: The prevalence of chronic diseases continues to rise. Indonesian health insurance covers the costs of outpatients with chronic diseases. Patient with chronic disease tends to use complex medicines, which impact the cost.Objective: This research aimed to determine medicine costs, claims, the effect of the number of medicines, the type of clinics and the presence of secondary diagnoses on medicine costs. Methods: This research used a quantitative descriptive method and was conducted at Prof. Dr. Chairuddin P. Lubis Hospital in Indonesia. Data were collected from outpatient prescriptions of chronic disease patients in 2023 at the national health insurance services. The data were analyzed using SPSS Version 22 and presented as numbers and percentages.Results: The results were the average medicine cost of IDR 218.782.13, the average claims of IDR 206.702.95, and additional medicine claims of IDR 170.847.84. The burden of medicine costs on claims reached 57.95%. The number of medicines and secondary diagnoses did not affect medicine costs. The type of clinic significantly affects medicine costs.Conclusion: Chronic disease results in high medicine costs. Hospitals had to manage the medicine costs and claims well, especially in clinics, contributing to high medicine costs. Keywords: chronic disease; claims; hospital; medicine costs; national health insurance